Harry O'Connell, maritime labour and the racialised politics of place. (January 2016) - Featherstone, David
This article explores the forms of activism forged by seafarers' organisers from the Caribbean in interwar Britain to problematise dominant ways of thinking about 'race', labour and place. It focuses on Guyanese Harry O'Connell, who was to become one of the most prominent organisers of Cardiff's multiethnic seafaring community in the 1920s and 1930s. He was influential in struggles against the forms of 'white labourism' adopted by the National Union of Seamen. A committed Communist, O'Connell drew on the networks of the Comintern-affiliated International of Seamen and Harbour Workers (ISH) and International Trade Union Committee of Negro Workers (ITUCNW) to contest such white labourism, whilst simultaneously negotiating the racialised forms of internationalism constituted through Communist networks. The piece contributes to a broader 'reparative' approach to history which explores the terms on which labour, space and place are articulated.